Mechanism of Concerted Inhibition of α(2)β(2)-type Hetero-oligomeric Aspartate Kinase from Corynebacterium glutamicum - Yoshida, Ayako (American Society for Biochemistry and Molecular Biology, 2010)
Aspartate kinase (AK) is the first and committed enzyme of the biosynthetic pathway producing aspartate family amino acids, lysine, threonine, and methionine. AK from Corynebacterium glutamicum (CgAK), a bacterium used for industrial fermentation of amino acids, including glutamate and lysine, is inhibited by lysine and threonine in a concerted manner. To elucidate the mechanism of this unique regulation in CgAK, we determined the crystal structures in several forms: an inhibitory form complexed with both lysine and threonine, an active form complexed with only threonine, and a feedback inhibition-resistant mutant (S301F) complexed with both lysine and threonine. CgAK has a characteristic α(2)β(2)-type heterotetrameric structure made up of two α subunits and two β subunits. Comparison of the crystal structures between inhibitory and active forms revealed that binding inhibitors causes a conformational change to a closed inhibitory form, and the interaction between the catalytic domain in the α subunit and β subunit (regulatory subunit) is a key event for stabilizing the inhibitory form. This study shows not only the first crystal structures of α(2)β(2)-type AK but also the mechanism of concerted inhibition in CgAK.